2010
DOI: 10.1097/sga.0b013e3181e26ec2
|View full text |Cite
|
Sign up to set email alerts
|

Serum Electrolyte Shifts Following Administration of Sodium Phosphates Enema

Abstract: The misuse of sodium phosphates enemas has resulted in reports of potentially severe metabolic and hemodynamic disturbances. Despite their long availability, these products have not been fully characterized pharmacokinetically. This trial sought to evaluate changes in the metabolic and hemodynamic parameters following the administration of one of two standard sodium phosphates enemas. Enema Casen (250 ml) is available only in Spain, and Fleet Enema (133 ml) is available in 66 countries in six continents of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…A literature review showed that complications after enemas are also more common in children with gastroenterological conditions; for example, Hirschsprung's disease [17]. Yet, most of the reported severe adverse events were because of overdose, simultaneous admission of oral and rectal laxatives, or other contraindications [18]. Our patient presents an extremely rare case of developing typical side effects with no coexisting conditions.…”
Section: Discussionmentioning
confidence: 76%
“…A literature review showed that complications after enemas are also more common in children with gastroenterological conditions; for example, Hirschsprung's disease [17]. Yet, most of the reported severe adverse events were because of overdose, simultaneous admission of oral and rectal laxatives, or other contraindications [18]. Our patient presents an extremely rare case of developing typical side effects with no coexisting conditions.…”
Section: Discussionmentioning
confidence: 76%
“…The volume and formulation of enema had no additional impact on this relationship. All serum calcium concentrations remained in the normal range (2.12-2.64 mmol/L; 8.5-10.6 mg/dL) [30].…”
Section: Observational Studies and Clinical Trials Of Effects On Elec...mentioning
confidence: 85%
“…Two studies [29,30] evaluated a Spanish phosphate enema preparation, Enema Casen (250 mL, containing 35.5 g monobasic sodium phosphate monohydrate and 17.8 g dibasic sodium phosphate dodecahydrate; a total of 304 mmol phosphate). The first compared the effects of Enema Casen with no treatment in a cross-over study in 24 volunteers aged 35-70 years [29].…”
Section: Observational Studies and Clinical Trials Of Effects On Elec...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, it had been erroneously postulated that phosphate contained in an enema was poorly absorbed, underestimating the fact that retention times may count even more than the absolute dose [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%